Family Firm Reputation and Humanization: Consumers and the Trust Advantage of Family Firms Under Different Conditions of Brand Familiarity. (December 2018) - Beck, Susanne; Prügl, Reinhard
Pioneering conceptual and empirical work ascribe a trust advantage to family firms compared with their nonfamily analogies. But it remains unknown if this trust advantage persists with varying degrees of consumers' brand familiarity. Furthermore, the underlying cognitive mechanisms in the minds of consumers that trigger the trust advantage remain unexplored. Using mixed methods, four studies indicate that family firms' trust advantage does prevail in the context of real and familiar brands, and the strength of consumers' perception of an organization as a human being (i.e., humanization) explains higher levels of benevolence and trust attributed to family firms.